Efektivitas Relaxing Breathing Exercise Terhadap Kualitas Tidur dan Kontrol Kadar Gula Darah Pada Pasien Diabetes Melitus Kronik: Tinjauan Literatur - Jesus, Dionencia Nahak De; Prabawati, Dewi (Jurnal Keperawatan Florence Nightingale, 2025)
Background: This literature review study is motivated by the phenomenon of insomnia in patients with diabetes mellitus which is getting more serious over time and has an impact on sleep quality. Relaxation techniques are needed, namely relaxing breathing exercises, which can affect sleep quality and can cause endocrine and metabolic disorders such as glucose tolerance disorders, insulin resistance and reduced response to insulin. Objective: to see the effectiveness of relaxing breathing exercises on sleep quality in patients with diabetes mellitus. Method: A literature review was conducted on seven articles obtained from three databases, Proquest, Google Scholar and Pubmed. The keywords for searching articles are "diabetes mellitus", "exercise", "sleep quality", "blood sugar", "patients" and "hospitals" with "AND" and "OR" as Boolean operators. Results: From this literature review, it was found that relaxing breathing exercises have an effect or impact on sleep quality in patients with diabetes mellitus. The results of the review article are: 1) improved sleep quality, 2) increased performance scores and reduced stress levels, 3) improved internal relaxation during or after simulation sessions, and 5) improved sleep quality and healthy lifestyles. The results of the literature review prove that there is an effectiveness in improving sleep quality in patients with diabetes mellitus. Conclusion: Relaxing breathing exercise is effective in patients with diabetes mellitus. The recommendation of this literature review can make relaxing breathing exercise an alternative therapy used in patients with diabetes melitus